Manufacture of Gambir Leaf Press Impac System in Efforts to Increase Productivity of Gambir Farmers - Erizon, Nelvi; Jasman, Jasman; syahrul, syahrul; Wakhinuddin, Wakhinuddin (Teknomekanik, 2019)
The Hipgampra farmer group has Gambir farming land. The problems that occur in this farmer group have not had a press tool, usually, this farmer group rents gambir leaf processing equipment privately and must pay rent wages which are worth one-third of the proceeds of the sale. Through this service activity, the team wanted to overcome the problem by giving a press tool to process gambir leaves. The purpose of the implementation of this service activity is to provide a solution to the problems faced by gambier women in the process of pressing gambier leaves. The method of applying science and technology carried out in this activity is to provide introductory theories, demonstrations, and practices. The introductory theory is applicable, namely the introduction of tools, how to use them, their functions and application applications in the field. The realization of service to the community of Kenagarian Lampanjang Sutera Pesisir Selatan Subdistrict was held on October 6, 2018. The equipment that was handed over to the community of Kenagarian Lampanjang Subdistrict, Sutera in the form of a unit of a Gambir leaf impact system. Application of appropriate technology that is applied to gambir leaf processing must be adjusted to the productivity of harvested gambier leaves. The number of gambir leaves that can be harvested by gambier farmers will adjust the capacity of the gambir leaf press to be processed. The tool that is devoted to the community has a forging foundation that functions as a place for gambir leaves to be pressed and has a jack stand that will press the gambir leaves to the foundation so that the sap of gambier will come out.